Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1289/ehp.7727
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Pneumonitis Associated with Environmental Mycobacteria

Abstract: A previously healthy man working as a machine operator in an automotive factory developed respiratory symptoms. Medical evaluation showed abnormal pulmonary function tests, a lung biopsy showed hypersensitivity pneumonitis, and his illness was traced to his work environment. His physician asked the employer to remove him from exposure to metalworking fluids. Symptoms reoccurred when he was later reexposed to metalworking fluids, and further permanent decrement in his lung function occurred. Investigation of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…Although asthma and dermatitis seem to be caused by the chemical toxicity of MWFs due to additional components (e.g., biocides, defoamers, corrosion inhibitors, or dyes) (22,33,38), MOL has been related to microorganisms that frequently contaminate MWFs, especially Mycobacterium immunogenum, a recently described, fast-growing mycobacterium included in the Mycobacterium chelonae-Mycobacterium abscessus complex (18,24,37,48,52,54). Arguments in favor of this etiology are the presence of specific precipitins in MWF-related HP cases (5,14,32) and/or the presence of M. immunogenum in their environment (4,18,42,52). The ability to induce HP in mice exposed intranasally to M. immunogenum (16,40) is evidence of the role of this microorganism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although asthma and dermatitis seem to be caused by the chemical toxicity of MWFs due to additional components (e.g., biocides, defoamers, corrosion inhibitors, or dyes) (22,33,38), MOL has been related to microorganisms that frequently contaminate MWFs, especially Mycobacterium immunogenum, a recently described, fast-growing mycobacterium included in the Mycobacterium chelonae-Mycobacterium abscessus complex (18,24,37,48,52,54). Arguments in favor of this etiology are the presence of specific precipitins in MWF-related HP cases (5,14,32) and/or the presence of M. immunogenum in their environment (4,18,42,52). The ability to induce HP in mice exposed intranasally to M. immunogenum (16,40) is evidence of the role of this microorganism.…”
mentioning
confidence: 99%
“…Since the first reports (5,27), most described cases of MWFrelated HP have been in the U.S. automotive industry (4,18,20,24,28,32,37,42,56). The first European case clusters were recently reported in automotive plants in Great Britain (8) and in France (41).…”
mentioning
confidence: 99%
“…described 12 cases (2003-2004) of MWF-associated HP who had precipitins against Acinetobacter and Ochrobactrum, but precipitins were also present in a similar proportion of exposed control workers without disease at the same plant. Many of MWF-associated HP cases were linked to MWF containing nontuberculous RGM [21,24,[27][28][29]. WILSON et al [4] and WALLACE et al [24] showed that 95% of mycobacterial isolates recovered from industrial MWF in plants with cases of machinist HP belong to M. immunogenum.…”
Section: Subjectsmentioning
confidence: 99%
“…HP is caused by the inhalation of a wide variety of antigenic particles small enough to reach the alveoli, comprised of microbial, animal, or insect proteins and other constituents. Environmental mycobacteria of the M. chelonae-M. abscessus (MCA) group -particularly M. immunogenum -have been associated with outbreaks of HP in factory workers inhalationally exposed to contaminated metalworking fluid (MWF) aerosols (Kreiss & Cox-Ganser 1997;Moore et al 2000;Wilson et al 2001;Falkinham 2003;Beckett et al 2005;Tillie-Leblond et al 2011). HP cases presenting variable clinical forms (acute, subacute, chronic) have been observed in machinists exposed to contaminated MWF (Freeman et al 1998;Zacharisen et al 1998;Beckett et al 2005;Rosenman 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental mycobacteria of the M. chelonae-M. abscessus (MCA) group -particularly M. immunogenum -have been associated with outbreaks of HP in factory workers inhalationally exposed to contaminated metalworking fluid (MWF) aerosols (Kreiss & Cox-Ganser 1997;Moore et al 2000;Wilson et al 2001;Falkinham 2003;Beckett et al 2005;Tillie-Leblond et al 2011). HP cases presenting variable clinical forms (acute, subacute, chronic) have been observed in machinists exposed to contaminated MWF (Freeman et al 1998;Zacharisen et al 1998;Beckett et al 2005;Rosenman 2009). While there has been increasing interest in both clinical and research aspects of MWF-associated HP (Gupta et al 2009;Tillie-Leblond et al 2011;Roussel et al 2011;Burton et al 2012;Chandra et al 2013Chandra et al , 2015, differential diagnosis and immunological mechanisms of this occupational lung disease are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%